Formulation and Evaluation of Oral Disintegrating Tablets of Lornoxicam by 32 Factorial Design - Niranjan Bhadkwade, Swati Rawat, Upendra Galgatte (Journal of Applied Pharmaceutical Science, 2013)
Oral disintegrating dosage form provides an opportunity to manufacturers to extend product life cycle and to expand market. Oral disintegrating tablets (ODT) have this opportunity over conventional tablets. Lornoxicam is non steroidal anti-inflammatory drug and used in treatment of post traumatic pains, muscular and skeletal pains, joint disorder and rheumatic arthritis. Fast onset of action is required in these indications. Therefore it was thought to prepare ODT of Lornoxicam which would help to avoid first pass metabolism and to improve bioavailability as well. ODT were prepared by direct compression method by using crospovidone as superdisintegrating agent and optimized by 32 factorial design. Independent variables were concentration of crospovidone (X1) and hydroxypropyl cellulose (X2) while dependent variables were disintegration time and percent drug released. Optimised formulation, F4, showed drug content (97.90±0.37%), disintegration time (20.33±0.317 sec), percent drug released (101.5±0.59%), water absorption ratio (113.5±1.26%). This formulation was stable at 400C ±20C and RH 75%±5% for three months. Present study demonstrated potential for rapid absorption, improved bioavailability, effective therapy and patient compliance.
Keywords: Lornoxicam, ODT, superdisintegrant, direct compressi